On Computation of Edge Degree-Based Banhatti Indices of a Certain Molecular Network - Jiang-Hua Tang; Muhammad Abid; Kashif Ali; Asfand Fahad; Muhammad Anwar Chaudhry; Muhammad Imran Qureshi; Jia-Bao Liu (Journal of Mathematics)
Chemical graph theory deals with the basic properties of a molecular graph. In graph theory, we correlate molecular descriptors to the properties of molecular structures. Here, we compute some Banhatti molecular descriptors for water-soluble dendritic unimolecular polyether micelle. Our results prove to be very significant to understand the behaviour of water-soluble dendritic unimolecular polyether micelle as a drug-delivery agent.